Alasan berdirinya The Indonesia-Israel Public Affairs Committee di Indonesia - Gora Ardian Dwi Putra (HI 15 UMY 260, 2015)
*260 IIPAC under the dean, Benjamin Ketang, has a great purpose to do to compose the coop between Indonesia and Israel. Indonesia and Israel realized that they both mutually needs goods for industry developing. Cause Indonesia is the one of most biggest supplier of raw material in the world, and also Indonesia is a biggest potential market for Israel goods. But overall, existance of IIPAC was uncertainty, cause the stronge argument was came up from Jeremy Jones as official from Australia-Israel Jewish Affairs Council (AIJAC). He said, AIJAC don‟t know anything about IIPAC and not as ally of AIJAC like what Benjamin declared.